Tetracycline tethered to titanium inhibits colonization by Gram‐negative bacteria. Issue 7 (12th November 2014) - Davidson, Helen; Poon, Martin; Saunders, Ray; Shapiro, Irving M.; Hickok, Noreen J.; Adams, Christopher S.
Abstract: As peri‐prosthetic infection is one of the most devastating complications associated with implant placement, we have reasoned that such infection can be largely subverted by development of antibacterial implants. Our previous work demonstrated that covalent coupling of vancomycin to titanium alloy prevented colonization by the Gram‐positive pathogens, Staphylococcus aureus and Staphylococcus epidermidis . Some orthopedic devices, including permanent prosthesis anchors, and most dental implants are transcutaneous or transmucosal and can be prone to colonization by Gram‐negative pathogens. We report here the successful covalent coupling of the broad‐spectrum antibiotic, tetracycline (TET), to titanium surfaces (Ti‐TET) to retard Gram‐negative colonization. Synthetic progress was followed by changes in water contact angle, while the presence of TET was confirmed by immunofluorescence. Ti‐TET actively prevented colonization in the presence of bathing Escherichia coli, both by fluorescence microscopy and direct counting. Finally, the Ti‐TET surface supported osteoblastic cell adhesion and proliferation over a 72‐h period. Thus, this new surface offers a powerful means to protect transcutaneous implants from adhesion of Gram‐negative pathogens, decreasing the need for replacement of this hardware. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1381–1389, 2015.